(untitled) (Journal of Information Technologies in Education (ITE), 2019)
Modern methods of checking the knowledge quality, their application at different stages of training are considered. The opinions of experts about the advantages and disadvantages of using computer-based testing are analyzed. The results of the independent measurement of knowledge of agrarian college students on the platform LCMS MOODLE is presented. This measurement is annually conducted by the State Institution SMC ―Agroosvita‖. It is indicated regularities found in the subject analysis of the results of individual educational institutions. The cases of constantly low results in certain disciplines in comparison with other educational institutions are shown, ways of differentiated methodical support with the use of modern ICTs are suggested, the basic scheme of the interaction cycle among SMC "Agroosvita" and the educational institution for improving the quality of provided educational services is given. The instrumentarium for improving the quality of educational services is determined: independent computer-based testing on LCMS platforms, formation of a methodological complex on the basis of modern ICT tools and analysis of the results of the interaction between the educational institution and SMC ―Agroosvita‖. Ukrainian and Polish educational electronic repositories are compared as at November 2018. The emphasis is on the necessity to create and replenish modern methodological and teaching materials of national electronic databases